Arab Governance Report III - United Nations Economic; Social Commission for Western Asia (United Nations, 2018)
The third edition of the Arab Governance Report introduces post-war best practices from international and regional experiences. It suggests strategies and policies for Libya and Yemen that focus on the immediate aftermath once combat ceases and a future political settlement. With the prioritization and sequencing of post-war policies dependent on distinctive historical trajectories, these road maps are tailored to the unique circumstances of each case. The objective is to initiate debate on institution building and its role in supporting sustainable peace in both country contexts. It helps elucidate the design of post-conflict, consensus-based processes for reforming governance structures and rehabilitating key institutions after political settlement. The goal of effective institution building is to advance mechanisms to preserve and consolidate the peace process, and enhance State legitimacy through sustainably developing its capacity to take on the basic requirements of governance.